Encapsulation of Salmonella phage SL01 in alginate/carrageenan microcapsules as a delivery system and its application in vitro - Zhou, Yuqiao; Xu, Dingting; Yu, Haijie; Han, Jianzhong; Liu, Weilin; Qu, Daofeng (Frontiers in Microbiology, 2022)
Phages can be used successfully to treat pathogenic bacteria including zoonotic pathogens that colonize the intestines of animals and humans. However, low pH and digestive enzyme activity under harsh gastric conditions affect phage viability, thereby reducing their effectiveness. In this study, alginate (ALG)/κ-carrageenan (CG) microcapsules were developed to encapsulate and release phage under simulated gastrointestinal conditions. The effects of ALG and CG concentrations on the encapsulation and loading efficiency of microcapsules, as well as the release behavior and antibacterial effects of microcapsules in simulating human intestinal pH and temperature, were investigated. Based on various indicators, when the concentration of ALG and CG were 2.0 and 0.3%, respectively, the obtained microcapsules have high encapsulation efficiency, strong protection, and high release efficiency in simulated intestinal fluid. This effect is attributed to the formation of a more tightly packed biopolymer network within the composite microcapsules based on the measurements of their microstructure properties. Bead-encapsulation is a promising, reliable, and cost-effective method for the functional delivery of phage targeting intestinal bacteria.